Centre for Islamisation: spearheading the Islamisation mission of the University - Md. Noon, Hazizan; Abd. Rahman, Akmal Khuzairy (IIUM Press, 2019)
The chapter is about the rationales of establishing the centre to be the coordinator of Islamisation-related activities at the Kulliyyat, Centres, Divisions and Offices of IIUM. It is also meant to monitor and initiate activities related to the Islamisation mission of the IIUM.